Methods of Domestic and Foreign Representatives (Eurasian Journal of Learning and Academic Teaching, 2022)
Learning English, in fact, is a rather laborious process, so for normal education it is necessary to teach English by ordinary, orthodox methods, especially since a language institute has long been established in our country, and there are proven methods and techniques that can be used to study in present time. The only drawback of the past education system is the lack of attention to such a part of the English language as spoken English, the importance of which at the present stage cannot be underestimated